Local Wisdom of Tinuktuk Traditional Typical Food in the Simalungun Community - Liony Patricia Panjaitan; Asni Barus (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article is entitled “Local Wisdom of Tinuktuk Traditional Typical Food in the Simalungun Community”. Tinuktuk is a traditional food served in the form of chili sauce and made from crushed spices and is believed by the Simalungun people to have properties for curing various internal ailments. Making tinuktuk is passed down from generation to generation by ancestors. As science develops, the Simalungun people switch from traditional to modern medicine. The purpose of writing this thesis is to describe the stages of making tinuktuk traditional specialties, describe the benefits of consuming tinuktuk traditional specialties, describe efforts to preserve tinuktuk traditional specialties, describe local wisdom in tinuktuk traditional specialties. the method used is descriptive method. The theory used is the theory of local wisdom.